Sensitivity enhancement of chemical sensor using aligned-gap split ring resonator - Mat Rusni, Izyani; Ismail, Alyani; Hamidon, Mohd Nizar (Faculty of Sciences and Technology, University of El Qued, 2018)
A modified Split Ring Resonator named Aligned Gap Split Ring Resonator was experimentally presented as a sensing element for characterization of solvents at 4.89GHz microwave frequency. The results demonstrated a good agreement between simulation and fabrication measurement. The proposed sensor demonstrated a strong localized electric field at sensing area with high Q factor value of 240 which indicate a very good sensitivity of the sensor. The sensing approach was based on distinguishing a shift in resonance frequency of the sensor when a dielectric material is introduced at the gaps of the sensing element. A remarkable shifts of resonance frequencies with the maximum value of 400MHz were observed upon introduction of several solvents. The sensitivity of the sensor was obtained as 0.001/ɛ with respect to changes in permittivity value of the solvents.